(untitled) (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2021)
In North America, dental disease is the leading pediatric chronic illness. Poor oral health influences a child’s ability to speak, eat, and socialize and has been linked with heart disease, diabetes, and cancer. Despite overwhelming evidence that poor oral health can have lifelong and systemic influences on overall well-being, comprehensive oral health care has not been emphasized in nursing education. The purpose of this study was to explore third-year nursing students’ perceptions and experiences with pediatric oral health nursing education through an interpretive description approach. Data for analysis gathered in focus group interviews resulted in three main themes: nursing education is key: recognition of and insight into the value of oral health care; fading away: barriers to education and practice; and spreading the culture: improving nursing education and practice. The findings highlight a predominant culture in nursing education and practice in which knowledge and skill acquisition related to pediatric oral health is being neglected. Consequently, nursing students experience limited development of the basic knowledge, skills, and resources to adequately care for infants, children, and adolescents in a holistic and comprehensive manner. Effective strategies to improve nursing education include early integration of oral health concepts, demonstration and hands-on preparation of oral health care practices and assessment, and interprofessional oral health education.